Nomograms for metastasis of non-sentinel lymph nodes or more than three lymph nodes in patients with one or two positive sentinel lymph nodes - Wang, Xue-Er; Bi, Zhao; Zhang, Jin; Wang, Yong-Sheng (Frontiers in Oncology, 2024)
Purpose: Purpose was to provide advice for the indication of regional nodal irradiation (RNI) in patients with 1-2 positive sentinel lymph nodes (SLNs) without axillary lymph node dissection (ALND).We conducted a retrospective study in Shandong Cancer Hospital, Fudan University Shanghai Cancer Center, and West China Hospital. Logistic analysis was performed in order to explore the influencing factors of positive non-SLNs (NSLNs) and >3 positive nodes among patients with 1-2 SLNs+. Then nomograms were constructed.Results: Between May 2010 and 2020, among the 2,845 patients with 1-2 SLNs+ undergoing ALND (1,992 patients in the training set, and 853 patients in the validation set), there were 34.3% harbored NSLNs+, 15.6% harbored >3 positive nodes. Multivariate analysis showed that cN stage, number of positive/negative SLN, pathological tumor stage, lympho-vascular invasion (LVI), multicenter and molecular subtypes were significantly associated with NSLN metastasis. Similarly, multivariate analysis also showed that cN stage, number of positive/negative SLNs, pathological tumor stage, and LVI could be independent predictors of >3 positive nodes. Then, nomograms for NSLNs metastasis and >3 positive nodes were constructed using these parameters, respectively.The nomograms will be useful in estimating positive NSLNs and >3 positive nodes, and they might provide advice for the optimization of RNI.